PV-Transformer-Less Inverter Topology for Battery-Equivalent DC Supply from Leakage Current - Md. N. H. Khan; Md. T. Anowar; Md. D. Hossen; Md. M. Alam; K. J. Ahmad (Institute of Advanced Engineering and Science, 2016)
Solar panels used for electricity generation have got inverters as their core components. Such inverters are made from switching devices coupled with additional circuit component configured in a transformer-less topology in recent reported works. A transformer-less topology suffers from the drawbacks of lack of isolation leading to leakage current flow from various points of it down to ground. The leakage in inverters might be troublesome as it may lead to loss in power, and may cause malfunctioning of analog devices normally used in power inverters. In this work, we identify possible leakage currents in a given transformer-less topology using the circuit analysis principles. The conversion of so obtained leakage currents into a useful DC voltage is carried out in this work. This work focuses on converting leakage current into small DC voltage in the range of 1.1004V using recently reported rectifier circuits, supplying a load of 200Ω in the mW range. Although small in magnitude, such voltage sources could be used for battery charging purposes or driving small loads.